2006
DOI: 10.1136/bjsm.2006.033167
|View full text |Cite
|
Sign up to set email alerts
|

A 6-month prospective study of injury in Gaelic football

Abstract: Objective: To describe the injury incidence in Gaelic football. Methods: A total of 83 players from three counties were interviewed monthly about their injury experience, during the 6 months of the playing season. Results: The injury rate was 13.5/1000 h exposure to Gaelic football (95% CI, 10.9 to 16.6). There were nearly twice as many injuries during matches (64.4%, 95% CI, 54.1 to 73.6) as in training (35.6%, 95% CI, 26.4 to 49.5). The ankle was found to be the most commonly injured site (13.3%, 95% CI, 7.8… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

5
60
1
1

Year Published

2011
2011
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 50 publications
(67 citation statements)
references
References 16 publications
5
60
1
1
Order By: Relevance
“…This trend is also reported in adult Gaelic games 1,5,12 and other adolescent sports 20,21 and is attributed to the higher intensity, physicality and effort in a competitive match. 1,5 Adolescent players had a similar training injury rate as adolescent Gaelic footballers observed by Watson 13 (3.1 per 1000 h). Adolescent Gaelic footballers presented with a higher match injury rate than high school soccer players (7.2 injuries per 1000 h).…”
Section: Discussionsupporting
confidence: 56%
See 1 more Smart Citation
“…This trend is also reported in adult Gaelic games 1,5,12 and other adolescent sports 20,21 and is attributed to the higher intensity, physicality and effort in a competitive match. 1,5 Adolescent players had a similar training injury rate as adolescent Gaelic footballers observed by Watson 13 (3.1 per 1000 h). Adolescent Gaelic footballers presented with a higher match injury rate than high school soccer players (7.2 injuries per 1000 h).…”
Section: Discussionsupporting
confidence: 56%
“…They last up to 60 min for adolescent players and consist of two opposing teams of 15 players (goalkeeper, six defenders, two midfielders and six forwards). 1,2 Gaelic games are played on a rectangular field (length 130-145 m, width 80-90 m) and are multidirectional contact games that necessitate players performing at a high level of intensity and velocity. 3 Gaelic football has been described as a mixture of soccer and rugby and is similar to Australian Rules football.…”
Section: Introductionmentioning
confidence: 99%
“…7 To our knowledge, no authors to date have investigated the intrarater reliability of the adductor squeeze test in asymptomatic Gaelic Games athletes using a In addition to computing ICC values, we also undertook statistical analysis to determine if maximum squeeze values differed among the 3 test positions. On both days, the mean squeeze value was higher at 45°of hip flexion than at 0°and 90°of hip flexion (Table 2).…”
Section: Discussionmentioning
confidence: 99%
“…Both are collision-contact sports with speed, strength, and agility demands similar to those of Australian rules football, rugby union and rugby league, field hockey, and lacrosse. These games are played at high speed, which, when combined with significant physical contact, acceleration, deceleration, and turning, has been proposed 7 to increase the likelihood of injury during the season. Newell et al 8 demonstrated that 65% of Gaelic football intercounty players were unable to fully participate in training/ games for I to 3 weeks in a typical season as a result of injury.…”
mentioning
confidence: 99%
“…In many ways, Australian rules football is similar to soccer 4,5 and Gaelic football 5,6 and involves a combination of repetitive, high-intensity activities such as kicking, 7,8 sprinting, and jumping. These activities not only are physically demanding on players but carry a potential bias toward the use of trunk and hip flexor muscles.…”
mentioning
confidence: 99%